SIFAT FISIK DAN SENSORIS BUBUK ASAM JAWA YANG DIPRODUKSI MENGGUNAKAN BAHAN PENGISI PATI SINGKONG GAJAH DENGAN METODE FOAM-MAT DRYING - Yunita Prasasti, Elisa; Prabowo, Sulistyo; Rachmawati, Maulida; Andriyani, Yulian (Jurnal Pengolahan Pangan, 2023)
Powder is a processed food product in the form of a fine powder, easily soluble in water, has a long shelf life and is practical. The problem that often arises in tamarind is that it has to separate the seeds and meat so that it is processed into powder. The purpose of this study was to determine the effect of adding filler concentration and foam-mat drying method on physical and sensory properties. This study is an experimental study of factorial RAL with 2 treatments and 3 replications. The first factor is the use of foam-mat drying method and without foaming, the second factor is the concentration of elephant cassava starch filler (10%, 15%, 20% and 25%). The data were analyzed using two way ANOVA and further tested using the Tukey test =5%. The results showed that the addition of cassava starch concentration as a filler and foam-mat drying method had a significant effect on water content, solubility, speed of dissolution by heating, precipitate, color test and sensory properties of tamarind powder.